Specifying Learners’ Professional Needs in Academic Writing - E. S. Chuikova (Высшее образование в России)
The article examines the controversial procedure of analyzing the learner’s professional needs. Needs analysis is generally regarded as an invaluable tool for constructing a course syllabus. It might be really informative if the target situation analysis and present situation analysis are combined. Speaking about academic writing teaching for Russian non-academic students at the Bachelor Degree level, one should admit that students have no or limited experience of functioning in an academic area in English. Consequently, their responses to the questionnaires as one of the frequently used methods of target situation analysis are merely assumptions; and the answers could not be taken as objective and valid. The author presents a system of analyzing students’ needs within the framework of Academic Writing course: namely, distinguishes the stages that precede or follow teacher-student talks about their expectations, provides more objective practice of examining learners’ needs, and discusses ways of improving question-answer sessions/ interviews. Needs analysis practice that develops learners’ professional needs involves task-based learning, reflexive activities, and teaching to ask good questions. Bringing into life the analogy between customer development theory in management and needs analysis practice in education, it is possible to work out a fruitful strategy. Conducting needs analysis pertains equally to specifying and developing students’ needs in academic communication.